Intrinsic laryngeal lipoma: a case report - Agarwal, Shubham; Sharma, Shivam; Singhal, Pawan; Gupta, Nishant (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Lipomas are the most common subcutaneous tumors. Intralaryngeal lipoma comprises 0.1% of all benign laryngeal tumors. Slow and insidious growth, for a long time; these may give rise to symptoms due to physical discomfort due to their size and compression on surrounding structures. Lipomas are benign mesenchymal tumors with rare localization in the upper aero-digestive tract. Intralaryngeal lipoma may present with clinical features including; feeling of a lump in the throat, cough and airway obstruction, stridor and dyspnea on exertion or even at rest may be present in more severe cases. We present a case of a 32 years old male patient with the complaint of gradually change of voice and dysphagia and difficulty in breathing on extreme physical activity for 5 months. Total removal of these lesions is important to avoid recurrences, a possibility that has been described in the Literature. The possibility of recurrence after long free-intervals should be borne in mind; thus, an extended period of long-term follow-up is mandatory.